Mixed Infection of Cytomegalovirus and Pulmonary Nocardiosis Caused by Nocardia elegans Diagnosed Using Nanopore Sequencing Technology - Watanabe, Chie; Kimizuka, Yoshifumi; Fujikura, Yuji; Hamamoto, Takaaki; Watanabe, Akira; Yaguchi, Takashi; Sano, Tomoya; Suematsu, Ryohei; Kato, Yoshiki; Miyata, Jun; Matsukuma, Susumu; Kawana, Akihiko (Internal Medicine, 2022)
A 69-year-old woman who had undergone renal transplantation and was receiving sulfamethoxazole/trimethoprim (ST) developed pulmonary nocardiosis. To our knowledge, this is the first report of the identification of Nocardia elegans using nanopore sequencing, supported by 16S rDNA capillary sequencing findings. Chest computed tomography performed after ST initiation revealed significant improvement of the pulmonary shadows compared to previous findings. We herein report the value of nanopore sequencing for rapid identification of rare pathogens, such as Nocardia elegans. Furthermore, our findings suggest that Nocardia may infect even patients receiving ST, which is currently the most effective prophylactic drug.